GAMBARAN KEHILANGAN GIGI SULUNG PADA SISWA MADRASAH IBTIDAIYAH DARUL ISTIQAMAH BAILANG - Mamonto, Eka Dewi Indriani; Wowor, Vonny N. S.; Gunawan, Paulina (UNIVERSITAS SAM RATULANGI, 2014)
Deciduous teeth as the permanent teeth have several functions, among others, as a means of mastication, speech synthesizers,aesthetic. In addition, primary teeth have a special function that is not owned by the permanent teeth. Deciduoustooth can serve as a guide for future permanent teeth to erupt into place so as to maintain the growth of the arch. Loss ofprimary teeth is a normal or physiological processes, but can also be caused by disease and trauma. Caries is a diseasethat most contribute to the deciduous tooth. The research was conducted on the students of Madrasah Darul IbtidayahIstiqamah Bailang students with a background of lower economic level. This study is a descriptive cross sectional method.This study population is all students aged 5-13 years with a total of 90 students. Sampling using total sampling methodthe number of samples that met the inclusion criteria as much as 64 samples. Research instrument used in the examinationform and interview. The results showed that many types of deciduous teeth suffered the loss of two deciduous molarsof the lower jaw (43%); loss of primary teeth is most prevalent at the time before the age of eruption of permanentteeth replacement (90%) for the upper jaw and (66%) for the lower jaw; region of the lower jaw the most (77.4%) whoexperienced a loss of primary teeth; and caries is a cause of loss of primary teeth the most common (86.6%) for the upperjaw and (91.2%) for the lower jaw.Keywords: Loss of primary teeth, Madrasah Students, Age eruption of the permanent teeth.Keywords: Loss of primary teeth, Madrasah Students, Age eruption of the permanent teeth